Taxation and capital structure: Empirical evidence from a quasi-experiment in China - An, Zhiyong (Journal of Corporate Finance, 2012)
China's new Corporate Income Tax Law was passed in March 2007 and took effect on January 1, 2008. It terminated the dual corporate income tax regime by removing the preferential tax treatments offered to foreign investment enterprises (FIEs) and unifying the corporate income tax regime for FIEs and Chinese domestic enterprises (DEs). This paper uses a difference-in-differences approach to determine whether FIEs responded to the law by raising debt ratios. Employing the Chinese Industrial Enterprises Database from 2002 to 2008 to implement the analysis, we find that FIEs have responded to the law by raising debt ratios; the treatment effect is larger for Hong Kong–Macau–Taiwan (HMT) investment enterprises than for other FIEs, which implies that HMT investment enterprises are more sensitive and more responsive to the removal of the preferential tax treatments than other FIEs; and the treatment effect by restricting the control group to State-Owned Enterprises (SOEs) is less than that by restricting the control group to Private-Owned Enterprises (POEs), which is consistent with the perception that SOEs might enjoy more favorable treatments from the Chinese government than POEs. All three findings are consistent with the tax-based theories of capital structure, and hence we conclude that taxation plays an important role in the choice of capital structure. We argue that our conclusion is not China-specific, but a general lesson for modern finance theory and is portable to developed countries.